-5(2x+6)=-3(-4+x0

Simple and best practice solution for -5(2x+6)=-3(-4+x0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2x+6)=-3(-4+x0 equation:



-5(2x+6)=-3(-4+x0
We move all terms to the left:
-5(2x+6)-(-3(-4+x0)=0
We add all the numbers together, and all the variables
-5(2x+6)-(-3(x-4)=0
We multiply parentheses
-10x-(-3(x-4)-30=0

See similar equations:

| (7x2)=69 | | 9e+4=14+8e9e+4=14+8e | | 9=1-2s | | 2y-2=-2-4y | | 10=0.50(20)=b | | 7/2q=35 | | 9=6k | | 2(3x+12)=6x+12 | | F(4y)=-2•4y-3 | | 3(-1)-2y=0 | | 6(3r-5/2)+4=52 | | 5x(4x+2)-3x+2=-144 | | Y=(x+7)2=69 | | 6(3r-5)/2)+4=52 | | 6x2-24x=0 | | —x^2+16=0 | | -12-m=-3m+1-12m | | 3d+56=d+17 | | 2q+10-14q+60=21 | | y=0.75+4.87 | | −w20=−2.5 | | x÷2-3=2 | | 2w^2+9W=-9w | | 6x2-23x-4=0 | | 2a+5a-3=0 | | 14z^2+19z-3=0 | | 295.40=170+0.57x | | .50c+1.50c=206.50 | | 5/12-1/3x=5x/3 | | 2x+(-3)=7 | | 4x-9=6-6 | | 8h+9=11h |

Equations solver categories